2002
DOI: 10.1080/09533710022149395
|View full text |Cite
|
Sign up to set email alerts
|

Generation of reactive oxygen species in blood platelets

Abstract: The generation of superoxide anion radicals (O2*-) and the other reactive oxygen species (ROS) was estimated by means of cytochrome c reduction and chemiluminescence, as well in resting blood platelets and in platelets stimulated by thrombin in the presence or absence of some inhibitors of pathways involved in platelet activation. We used allopurinol (xanthine oxidase inhibitor), wortmannin (PI 3-kinase inhibitor) and staurosporine (protein kinase C inhibitor). To determine the involvement of the glutathione i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
111
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(119 citation statements)
references
References 34 publications
4
111
0
1
Order By: Relevance
“…Interestingly, ROS derived from platelet activation also plays an important role in signaling upon collagen-induced platelet aggregation. Free radical species act as secondary messengers that increase cytosolic Ca 2+ during the initial phase of platelet activation processes, and PKC is involved in receptor-mediated ROS production in platelets (36). Previous studies also showed that ROS formation is involved in collageninduced platelet aggregation, which is dependent on AA release and its metabolism (34); thus, ROS may be needed for platelet activation (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, ROS derived from platelet activation also plays an important role in signaling upon collagen-induced platelet aggregation. Free radical species act as secondary messengers that increase cytosolic Ca 2+ during the initial phase of platelet activation processes, and PKC is involved in receptor-mediated ROS production in platelets (36). Previous studies also showed that ROS formation is involved in collageninduced platelet aggregation, which is dependent on AA release and its metabolism (34); thus, ROS may be needed for platelet activation (37).…”
Section: Discussionmentioning
confidence: 99%
“…Glucose flux through AR is well recognized to generate oxidative stress by several mechanisms, including NADPH depletion, decreasing glutathione (GSH) levels (NADPH is the cofactor for GSH reductase that regenerates GSH from GSH disulfide [GSSG]), and increasing advanced glycation end products, generating ROS (10). Previous studies have demonstrated that TXA 2 biosynthesis is upregulated by oxidant formation (e.g., hydrogen peroxide) during platelet aggregation (34)(35)(36). We and others (16,20) have demonstrated that hyperglycemia increases oxidative stress in platelets.…”
Section: Discussionmentioning
confidence: 99%
“…In platelets, MDA is synthesized from arachidonic acid in equivalent amounts with thromboxane A 2 and derived thomboxane B 2 (25,30 ). However, much greater amounts of MDA are formed in peroxidation processes of other platelet lipids (31 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the direct effects of reactive oxygen species (ROS) on platelets are inconsistent with previous studies reporting both pro-and anti-aggregatory effects when platelets are exposed to exogenous ROS [15]. Oxidant stress generated either by platelets themselves via several intracellular sources [16] or by the artery wall can also modulate vascular tone [17] and this has implications for blood flow and thrombus formation within blood vessels.…”
Section: Introductionmentioning
confidence: 98%